Exploring the Role of Micro-Influencers in Influencing Tourist Perception of Arjasa Traditional Village, Jember Regency - Rusli Akhmad Junaedi; Muhammad Fikri; Muhammad Nauval Ikbar (Program Studi Pariwisata Fakultas Ilmu Budaya Universitas Gadjah Mada Yogyakarta, 2026)
Social media acts as the primary catalyst changing how travel destinations are marketed and consumed in the era of digital disruption. This study investigates how the community and managers of Arjasa Traditional Village view the role of micro-influencers in building images and drawing visits. Researchers utilize a qualitative approach with interpretive phenomenological research to capture the subjective experiences of local actors. Data was gathered through participatory observation and in-depth interviews with 9 informants including village leaders, MSME owners, and digital creators. Results show that micro-influencers provide the ability to convey authenticity and build high trust through personal communication. Using these digital agents in marketing strategies is vital for developing a positive village image and driving organic visits.